2012
DOI: 10.1007/s00432-012-1200-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and ratio disruption of ΔNp63 and TAp63 isoform equilibrium in endometrial adenocarcinoma: correlation with obesity, menopause, and grade I/II tumors

Abstract: These results indicate that both p63 isoforms and especially ΔNp63 play an important role in the development and progression of grade I/II endometrial adenocarcinoma, especially in obese and late-menopause women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
(27 reference statements)
0
9
0
1
Order By: Relevance
“…[40,70] In addition, a recent report indicated that p63 plays important roles in the development and progression of grade I/II endometrial adenocarcinoma. [71] It has been suggested that dysregulated expression of p63 is often correlated with amplification of its genomic locus, 3q27-28 and is frequently occurred in human epithelial cancers. [40] Studies on a cohort of 245 esophageal tumors showed that both TAp63 and ΔNp63 isoforms were upregulated at the transcriptional level in squamous cell carcinoma.…”
Section: P63 In Cancersmentioning
confidence: 99%
“…[40,70] In addition, a recent report indicated that p63 plays important roles in the development and progression of grade I/II endometrial adenocarcinoma. [71] It has been suggested that dysregulated expression of p63 is often correlated with amplification of its genomic locus, 3q27-28 and is frequently occurred in human epithelial cancers. [40] Studies on a cohort of 245 esophageal tumors showed that both TAp63 and ΔNp63 isoforms were upregulated at the transcriptional level in squamous cell carcinoma.…”
Section: P63 In Cancersmentioning
confidence: 99%
“…From this result, we hypothesized whether not only the overexpression of ΔNp63, but also the imbalance of p63, is associated with cervical cancer carcinogenesis. Vakonaki et al reported that an imbalance of the ΔNp63 and TAp63 isoforms is associated with grade I/II tumors in endometrial adenocarcinoma in a study of 20 paired adjacent normal and cancer tissues [23]. Therefore, we investigated the imbalance of p63, defined as the ΔN/TAp63 mRNA expression ratio, in cervical cancer cell lines and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, deletions, mutations and interactions with cellular or viral proteins have been recognized as key steps in the development of approximately half of all human cancers. Moreover, the TAp63 isoform had p53-like functions, whereas DNp63 functioned as a dominant negative inhibitor of the p53 family [18,19], which raises the question as to whether patients with TP63 mutations have an increased tumor incidence. However, there was no increased tumor incidence in our patients.…”
Section: Discussionmentioning
confidence: 99%